2012
DOI: 10.1088/0029-5515/52/7/074012
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric currents and their role during ELM formation in JET

Abstract: A recently developed numerical model, describing a self-amplification and structure formation process which is used to model the initial non-linear growth phase of edge-localized modes (ELMs), is applied to the JET tokamak. Connection length simulations of the magnetic topology, including only error fields, for JET reveal the existence of small, so-called short connection length flux tubes. Such a configuration is used as the starting point for the model. Thermoelectric currents are assumed to flow in the shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…The thermoelectric current model [29] describes the nonlinear evolution of an ELM. Its application for DIII-D and JET [6,28] shows good agreement with measurements. The model is based on the concept that an initial heat pulse triggers thermoelectric currents, through short connection length flux tubes [30].…”
Section: Interpretation Based On the Thermoelectric Current Modelsupporting
confidence: 55%
See 1 more Smart Citation
“…The thermoelectric current model [29] describes the nonlinear evolution of an ELM. Its application for DIII-D and JET [6,28] shows good agreement with measurements. The model is based on the concept that an initial heat pulse triggers thermoelectric currents, through short connection length flux tubes [30].…”
Section: Interpretation Based On the Thermoelectric Current Modelsupporting
confidence: 55%
“…This demonstrates the dynamic nature of the observed structures. It has been reported that additional thermoelectric currents in the plasma edge during the onset of an ELM can lead to the formation of such dynamic footprint patterns [6,28].…”
Section: Pre-elm Structures Versus Radially Propagating Elm Filamentsmentioning
confidence: 99%
“…As will be discussed in the next subsection, the ergodization does not need to be produced by current carrying filaments since it can be produced by the magnetic fluctuations associated with the ballooning mode itself. In the case of current carrying filaments, these currents are either thermoelectric in nature, localized by intrinsic error fields [62,63], or due to the dynamo effect [64]. These models find that the plasma edge can be ergodized, and manifold structures form, when localized currents of 200-300 A are present.…”
Section: The Role Of Ergodizationmentioning
confidence: 99%
“…This will allow for a more thorough comparison of the ELM simulations based on the presented model and ELMs observed in DIII-D. The model was recently tested on JET discharge 79459, which fits into the large distance regime, with very good agreement between observed ELM heat flux and field line penetration depth structures on both targets [24].…”
Section: Discussionmentioning
confidence: 83%